Association between previous work experience in general healthcare and recovery orientation among mental health professionals during the COVID-19 pandemic in Japan - Miharu Nakanishi; Tomohiro Takahashi; Keita Toshi; Mai Sakai; Hatsumi Yoshii (Discover Global Society)
Abstract Recovery orientation constitutes a core competency in mental health professionals. Working with primary care helps professionals learn and translate the concept of recovery into practice. In Japan where primary care system is not established yet, previous work experience in general healthcare may substitute for the absence of primary care work experience. However, the evidence quantifying the association is limited. We investigated the association between work experience in general healthcare and recovery orientation. We conducted a cross-sectional online questionnaire survey of hospital workers in Japan between July 2022 and March 2023. Sixty-two participants responded about the level of recovery orientation, personal stigma against people with mental illness, completion of on-the-job training courses, and the impact of the COVID-19 pandemic on their practice. Poor recovery orientation was significantly associated with previous work experience in general healthcare and worse stigma. Participants remarked that pandemic-related measures challenged discharge planning and person-centred practices. Their poor recovery orientation may reflect prioritizing patient safety in inpatient care settings, that could be compounded by the dilemma between infection measures and their mission as mental health organisations during the pandemic. In conclusion, mental health professionals with general healthcare work experience should be prioritised in educational initiatives. Modifiable factors for personal stigma need further clarification. Mental health policies should also reflect on the challenges that COVID-19 poses to hospital-based services.